Senecio sennikovii, a new replacement name for the Mexican endemic Senecio bracteatus Klatt (Asteraceae: Senecioneae) - Kottaimuthu, Ramalingam; Vimala, Murugan; Rajendran, Kuppu; Basu, Muthuramalingam Jothi (Phytotaxa, 2021)
The cosmopolitan genus Senecio Linnaeus (1753: 866) is one of the most species-rich genera in Asteraceae, comprising about 1426 species (POWO 2021); the main centres of its diversity are South Africa, Chile and the Mediterranean Basin (Calvo et al. 2015). About 63 species of Senecio are known to occur in Mexico, of which 44 species are endemic to the country (Villaseñor 2016).